2009
DOI: 10.1080/13803390802251378
|View full text |Cite
|
Sign up to set email alerts
|

An examination of decision making in bulimia nervosa

Abstract: This finding does not support the somatic marker hypothesis. Impaired decision making was associated with obsessive-compulsive traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 25 publications
4
57
2
5
Order By: Relevance
“…In BN, significant impairment was found in women with a diagnosis of BN compared to healthy controls, with IGT performance negatively correlated with bulimic symptomatology [11]. Failing to support the SMH, IGT deficits in BN patients were not associated with impaired anticipatory SCR [12]. Combining underweight and "weight-recovered" AN and BN participants, research found no significant differences between any of the eating disorder groups and controls on the IGT [9]; however, the eating disorder groups scored lower and lack of significance may be due to low statistical power.…”
Section: Decision Making and Eating Disordersmentioning
confidence: 90%
See 1 more Smart Citation
“…In BN, significant impairment was found in women with a diagnosis of BN compared to healthy controls, with IGT performance negatively correlated with bulimic symptomatology [11]. Failing to support the SMH, IGT deficits in BN patients were not associated with impaired anticipatory SCR [12]. Combining underweight and "weight-recovered" AN and BN participants, research found no significant differences between any of the eating disorder groups and controls on the IGT [9]; however, the eating disorder groups scored lower and lack of significance may be due to low statistical power.…”
Section: Decision Making and Eating Disordersmentioning
confidence: 90%
“…To further specify these decision making deficits in both obesity and other eating disorders, future studies should incorporate both the original and variant IGT (which reverses the task's reward contingencies), which would highlight whether deficits are due to hypersensitivity to reward, insensitivity to punishment, or a general "myopia" for future consequences both positive and negative, as is suggested here through the absence of strategy on the task. Similarly, research is required to investigate whether these shared deficits are related to impaired somatic marker signals as in AN [10] or unrelated to such signals as in BN [12], thus fully testing the premises of the SMH. The Dynamic Filtering Hypothesis [43,44], which offers a neural account of orbitofrontal cortex function with respect to monitoring and controlling emotion processing, could also be considered.…”
Section: Igt and Eating Disordersmentioning
confidence: 97%
“…Significant impairment was found in undergraduate women with BN, wherein IGT performance negatively correlated with bulimic symptomatology (Boeka & Lokkenz, 2006 ). A recent study found that female BN patients performed poorly on the IGT (Liao et al, 2009 ), but with no impairment in SCR (in contrast to results with AN; Tchanturia et al, 2007 ). In a comparison of AN females (who were either underweight or recovered to normal weight) and BN females, research found no signifi cant differences on the IGT between these eating disorder groups and controls (Bosanac et al, 2007 ).…”
Section: Brief Communicationmentioning
confidence: 98%
“…In addition, disorders associated with affective dysregulation such as e.g. pathological gambling (Cavedini et al, 2002b), addiction (Dom et al, 2006;Loeber et al, 2009), mania (Adida et al, 2008), borderline personality disorder (Haaland and Landro, 2007), obsessive-compulsive disorder (Cavedini et al, 2002a;Starcke et al, 2009), eating disorder (Cavedini et al, 2004;Liao et al, 2009), attention deficit hyperactivity disorder (Toplak et al, 2005) as well as a history of suicidality (Jollant et al, 2005) and sociopathic traits (Mitchell et al, 2002) have been associated with impaired performance in the IGT. Furthermore, there is a great deal of individual variability in IGT performance among healthy individuals.…”
Section: Introductionmentioning
confidence: 97%